2019
DOI: 10.1002/hbm.24779
|View full text |Cite
|
Sign up to set email alerts
|

Stria terminalis, amygdala, and temporoparietal junction networks facilitate efficient emotion processing under expectations

Abstract: Rapid emotion processing is an ecologically essential ability for survival in social environments in which threatening or advantageous encounters dynamically and rapidly occur. Efficient emotion recognition is subserved by different processes, depending on one's expectations; however, the underlying functional and structural circuitry is still poorly understood. In this study, we delineate brain networks that subserve fast recognition of emotion in situations either congruent or incongruent with prior expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Another study by Dzafic et al showed that greater ST microstructure was associated with faster recognition of anger following an anger cue during a dynamic emotional perception task (Dzafic et al, 2019). Their findings suggest that individuals with greater ST microstructure have more efficient emotion processing under threat (Dzafic et al, 2019). In the context of our findings, in which greater SED is associated with greater ST structural integrity, these studies suggest a potential neural adaptation in which greater ability to orient to threat or recognize emotion may yield enhanced situational awareness of threat, therefore enhancing likelihood of survival.…”
Section: Functional Implications Of Deprivation-related Enhanced Stria Terminalis Structural Integrity: a Potential Neural Adaptation?mentioning
confidence: 99%
See 2 more Smart Citations
“…Another study by Dzafic et al showed that greater ST microstructure was associated with faster recognition of anger following an anger cue during a dynamic emotional perception task (Dzafic et al, 2019). Their findings suggest that individuals with greater ST microstructure have more efficient emotion processing under threat (Dzafic et al, 2019). In the context of our findings, in which greater SED is associated with greater ST structural integrity, these studies suggest a potential neural adaptation in which greater ability to orient to threat or recognize emotion may yield enhanced situational awareness of threat, therefore enhancing likelihood of survival.…”
Section: Functional Implications Of Deprivation-related Enhanced Stria Terminalis Structural Integrity: a Potential Neural Adaptation?mentioning
confidence: 99%
“…Koller et al showed that greater ST FA is associated with greater orienting bias toward threat in a saccadic decision task (Koller et al, 2019). Another study by Dzafic et al showed that greater ST microstructure was associated with faster recognition of anger following an anger cue during a dynamic emotional perception task (Dzafic et al, 2019). Their findings suggest that individuals with greater ST microstructure have more efficient emotion processing under threat (Dzafic et al, 2019).…”
Section: Functional Implications Of Deprivation-related Enhanced Stria Terminalis Structural Integrity: a Potential Neural Adaptation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Seed PLS is a multivariate statistical method widely used to investigate the relation between activity in a selected brain region (seed voxel) and activity in the rest of the brain, across task conditions (McIntosh et al, 1997;Schreurs et al, 1997;McIntosh, 1999;Della-Maggiore et al, 2000). Based on previous evidence on the differential role of the anterior and posterior hippocampus in episodic memory retrieval (Poppenk et al, 2013), and on the findings from the whole-brain PLS analysis, functional seed values were extracted from a region of interest with a neighborhood size of one voxel (i.e., including the seed voxel plus one voxel adjacent to the peak voxel in each direction; see also Marstaller and Burianová, 2015;Ziaei et al, 2017;Dzafic et al, 2019) centered in the left anterior hippocampus (MNI coordinates: x = −30, y = −10, z = −20) and the left posterior hippocampus (MNI coordinates: x = −26, y = −26, z = −22), to examine, respectively, task-related functional connectivity during detection of memory targets (i.e., including hits in the incentiveold condition and CRs in the incentive-new condition in the analysis) and detection of items that were not the target of memory (i.e., including hits in the incentive-new condition and CRs in the incentive-old condition in the analysis). The analytical procedure for the seed PLS functional connectivity analysis was the following: first, the BOLD values from the hippocampal seed regions were extracted for each event of interest (detection of memory targets and non-targets) across 8 time points from the onset of the trial.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…Previous studies have reported that both anatomical (white matter [WM] tractography) and functional network efficiencies were related to cognitive intelligence (Li et al, 2009 ; van den Heuvel et al, 2009 ; Langer et al, 2012 ) and EI (Smith et al, 2018b ; Dzafic et al, 2019 ) in adolescence, adults, and elderly groups. However, most of them focused on one age group, and no study investigated whether, and how, the associations between the human brain network efficiency and intelligence changed from young adults to the middle-aged group.…”
Section: Introductionmentioning
confidence: 99%